Periodic rings with finitely generated underlying group - R. Khazal; S. Dascalescu (International Journal of Mathematics and Mathematical Sciences)
We study periodic rings that are finitely generated as groups. We prove several structure results. We classify periodic rings that are free of rank at most 2, and also periodic rings R such that R is finitely generated as a group and R/t(R)≃ℤ. In this way, we construct new classes of periodic rings. We also ask a question concerning the connection to periodic rings that are finitely generated as rings.